Metode Grafting Tanaman Tomat Menggunakan Batang Bawah Terong Untuk Mengatasi Genangan dan Mengendalikan Penyakit Tular Tanah di Kebun Percobaan Fakultas Pertanian Universitas Udayana - SUDIARTA, I PUTU; WIRYA, GUSTI NGURAH ALIT SUSANTA; WINANTARA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Grafting Method of Tomato using rootstock of eggplant to minimize problems caused by flooding and soil-borne diseases in Faculty of Agriculture Research Field Udayana University The study was conducted to determine the effectiveness of the Grafting Method of Tomato using rootstock of eggplant to minimize problems caused by flooding and soilborne diseases in Faculty of Agriculture Research Field Udayana University. The experimental design was used a Randomize bloc design (RBD), with 3 treatments including control and 9 replications. The treatments are, grafting, non-grafting and control usually use by the farmers. The first step of the research is grafting or tomato as a scion with eggplant as a rootstock. The grafting method was used is base one the AVRDC-method. The result showed the grafted tomato was free from wilting disease on the other hand the non-grafted tomato showed the symptom of wild diseases, the data indicated the grafted tomato was resistant by the soil-borne diseases including bacteria wilt as well as Fusarium wilt disease. For flooding we cannot compare the significantly result between grafted tomato and non-grafted tomato because the season is not wet season. The suggestion of this research is recommended to doing the research in wet season for more clear understand the effect of grafted tomato to the flooding.